ETIKA TABAYYUN DAN HIKMAH KOMUNIKASI PADA GRUP WHATSAPP MASJID: SEBUAH KAJIAN KOMUNIKASI ISLAM DALAM EKOSISTEM MEDIA KONVERGEN - Moh Syahri Sauma; Abdul Kohar (An-Nida' : Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study examines the ethics of tabayyun (verification) and hikmah (wise communication) in mosque WhatsApp groups within the ecosystem of convergent media. As religious communication increasingly shifts from physical mosque spaces to real-time digital interaction, WhatsApp groups have become important arenas for announcements, religious learning, fundraising, social coordination, and collective deliberation. However, this communicative expansion also increases the risks of misinformation, emotional escalation, over-forwarding, and symbolic harm within religious communities. Using a qualitative approach with a netnographic design combined with a multi-site case study, this research explores how tabayyun, hikmah, mau’izhah hasanah, and dialogical ethics are represented and operationalized in everyday digital interactions among mosque communities. The study is theoretically grounded in Islamic communication ethics, Qur’anic principles, Habermas’s communicative action theory, and McQuail’s media convergence framework. The findings conceptually show that mosque WhatsApp groups should not be treated merely as channels of information exchange, but as ethical communication ecosystems that require verification practices, empathetic reasoning, transparent moderation, and dignified discourse. The role of admins emerges as especially crucial in shaping discussion quality, conflict mediation, and the legitimacy of collective decisions. This study contributes both theoretically and practically by offering an operational framework for Islamic digital communication and by proposing communication governance tools such as verification checklists, polite clarification scripts, decision-summary formats, and moderation guidelines to strengthen public benefit, social trust, and the dignity of all congregants in digital religious communities.